2008
DOI: 10.1128/aac.01210-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Escherichia coli Lipopolysaccharide on Telithromycin Pharmacokinetics in Rats: Inhibition of Metabolism via CYP3A

Abstract: It has been reported that telithromycin is metabolized primarily via hepatic microsomal cytochrome P450 (CYP) 3A1/2 in rats and that the expression of hepatic and intestinal CYP3A decreases in rats pretreated with Escherichia coli lipopolysaccharide (ECLPS rats; an animal model of inflammation). Thus, it is possible that the area under the plasma concentration-time curve from 0 h to infinity (AUC 0-ؕ ) of intravenous and oral telithromycin is greater for ECLPS rats than for the controls. To assess this, the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…() demonstrated that an APR induced by the administration of E. coli LPS in rabbits decreased significantly the CYP content measured at 24 h after the first injection of endotoxin. Moreover, a significant decrease in hepatic and intestinal CYP3A was demonstrated in E. coli LPS‐treated rats, in which the endotoxin administration reduced the body clearance of telithromycin (Lee et al ., ). It has been proposed that suppressive effects of LPS on hepatic microsomal CYP are mediated through proinflammatory cytokines, such as TNF‐ α , IL‐1 β and IL‐6 (Monshouwer & Witkamp, ).…”
Section: Discussionmentioning
confidence: 97%
“…() demonstrated that an APR induced by the administration of E. coli LPS in rabbits decreased significantly the CYP content measured at 24 h after the first injection of endotoxin. Moreover, a significant decrease in hepatic and intestinal CYP3A was demonstrated in E. coli LPS‐treated rats, in which the endotoxin administration reduced the body clearance of telithromycin (Lee et al ., ). It has been proposed that suppressive effects of LPS on hepatic microsomal CYP are mediated through proinflammatory cytokines, such as TNF‐ α , IL‐1 β and IL‐6 (Monshouwer & Witkamp, ).…”
Section: Discussionmentioning
confidence: 97%
“…In cultured human hepatocytes, direct treatments with tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), interferon-γ (IFN-γ) and transforming growth factor-β (TGF-β) can reduce the expression of CYP1A2, CYP2C8 and CYP3A4 (13,14). In animals and humans, several studies or reports have shown the role of inflammation in reducing drug metabolism and CYP450 inhibition (15,16). CYP3A4 expression is transcriptionally regulated by pregnane X receptor (PXR), which is a ligand-dependent transcription factor (17).…”
Section: Discussionmentioning
confidence: 99%
“…The present results will play an important role in explaining the possible pharmacokinetic changes of mirodenafil and SK3541 in various rat disease models in which the CYP isoforms mentioned above are changed. For example, in rats with protein-calorie malnutrition (29), acute renal failure induced by uranyl nitrate (30), and diabetes mellitus induced by alloxan or streptozotocin (31), mutant Nagase analbuminemic rats, an animal model for human familial analbuminemia (32), and rats pretreated with lipopolysaccharide endotoxin induced by E. coli (33) or Klebsiella pneumoniae (34). These results could also contribute to explain possible drug-drug interactions between mirodenafil and other drugs which are primarily metabolized via hepatic CYP1A1/2, 2B1/2, 2D subfamily and/or 3A1/2.…”
Section: Discussionmentioning
confidence: 99%